Modelling the role of self-weight consolidation on the morphodynamics of accretional mudflats. (February 2016) - Zhou, Zeng; van der Wegen, Mick; Jagers, Bert; Coco, Giovanni
Abstract: We develop a consolidation module and merge it into a morphodynamic model to assess the role of consolidation on estuarine morphodynamics. We test the model using two settings: point models without hydrodynamic forcing to validate against two benchmark experimental datasets; and a profile model to simulate a mudflat restoration. The modelled self-weight consolidation influences the simulations by gradually reducing the bed level and decreasing the bed erodibility (i.e., increasing the critical bed shear stress). Both effects modify sediment transport processes on mudflats, leading to long-term morphodynamic effects. Depending on the initial bathymetry, the hydrodynamic forcing and the soil properties, the simulated morphological change of the restored mudflat may differ considerably with and without considering consolidation. The consolidation model developed can be utilised to assess the medium to long term effects related to estuarine development (e.g., wetland restoration) and aims to be a publicly available tool. Highlights: We develop a consolidation module for cohesive sediment based on Gibson's theory. We merge this consolidation module into a morphodynamic model. The consolidation model is validated against two settling column tests. Initial bathymetry, hydrodynamic forcing and soil properties affect consolidation. Consolidation cannot be neglected when mudflat restoration is simulated.